The Impact of Extended Family on Household Poverty in Korogwe Township - Lyimo-Macha, J. G.; Kaijage, J. M. (Tanzania Journal for Population studies and Development, 2009)
The objectives of this study, which was carried in Korogwe township, was to examine major constraints facing household members living in an extended family, identify number of households with extended and nuclear families, determine the number of dependants in households in an extended family, establish the contribution of extended families to household income and compare economic status between extended and nuclear families. The study adopted a cross-sectional design, administering a structured questionnaire to both members living in an extended family and nuclear family. It drew a representative sample of 120 respondents from a population of households in three wards, and analysed the resulting data statistically using SPSS, doing statistical tests using chi-square to test for statistical association between households with extended and nuclear family. The results show that household poverty influence the existence of extended family as people from poor families shift to moderate or wealthier families for assistance, or frequently request remittances. The study recommends reinforcement of a social welfare policy that can cope with the existing situation of extended families. There is also a need for education among heads households, especially on capital provision remittances as a coping strategy to problems that require frequent support from relatives. Furthermore, there is need for appropriate strategies to empower those who are in active labour but are not employed, especially in urban areas where employment is a big problem.